(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aimed to test the effectiveness of a counseling program in developing self-compassion and improving psychological well-being among recently divorced women. The sample of the study involved (40) recently divorced women, who were randomly distributed into two equal groups: control (20) and experimental (20). The tools of the study included the self-compassion scale which was developed by Hanoun & Al-Qaralah (2022), the psychological well-being scale that the researcher developed, and the counseling program that was based on some techniques and strategies of positive psychology, which was also prepared by the researcher. The results of the study indicated the effectiveness of the counseling program in developing self-compassion and improving psychological well-being among recently divorced women after its application. Among the most prominent recommendations was training newly divorced women to modify their thoughts through programs based on the techniques and strategies of positive psychology.